Моделювання дзеркальної антени з використанням гибридних методів розрахунку в програмі ANSYS HFSS - Масаликін, Д. І.; Свідерська, Л. І. (ХНУРЕ, 2025)
The article describes calculations of a reflector antenna using the HFSS program using both the basic finite element method and the methods of integral equations and physical optics. The implementation of various methods in one HFSS shell makes it possible to find a reasonable compromise between accuracy and calculation time when solving various problems, as well as to select individual structural elements calculate their characteristics in a certain way, and then apply hybridization.
Keywords: моделювання дзеркальної антени; ANSYS HFSS